Evaluation On The Properties Of Aggregate Subjected To Elevated Temperature Using Ncat Ignition Oven And Asphalt Mix Performance - Fuad, Khairul Ikhwan Mohd (Universiti Sains Malaysia, 2021)
Good and reliable asphalt pavement quality is essential to provide smooth road surfaces. A better-quality pavement provides a safer and comfortable ride for daily commute. Deteriorated road surface conditions might be due to the poor-quality aggregate used to prepare the asphalt mixture. Daily exposure to weathering effects degrades the asphalt mixtures. Therefore, determining the binder content of the asphalt mixture using the NCAT ignition oven prior to laying the mix is vital for decision-making criteria. Unfortunately, after the heating process, the aggregates were thrown away based on the critique that claims poor aggregate quality for those heated aggregates. Therefore, this research was conducted to quantify the quality of the heated aggregates. Virgin aggregate and heated aggregates were subjected to basic laboratory tests, including specific gravity test, aggregate crushing value (ACV) test, Los Angeles Abrasion Value (LAAV) test, and Marshall Stability and Flow tests. Additionally, both virgin and heated aggregate were used to prepare asphalt mixtures. The ACW14 asphalt mixtures were then subjected to laboratory tests to determine the Optimum Binder Content (OBC). The selected OBC was 5.2% for asphalt mixture prepared using the virgin aggregate (control sample). Meanwhile, the OBC for the asphalt mixture that used heated aggregate (modified sample) showed the OBC equal to 5.4%. It was hypothesized that an elevated temperature affected the strength of asphalt pavement properties. The results indicated that the apparent SG, SSD, and bulk SG for the modified sample recorded no significant difference compared to that of the control sample. However, the ACV of 32.6% was recorded for the modified sample, which is double from 17.0% of the ACV for control sample. The LAAV for the modified sample is significantly higher (59.5%) as compared to the control sample with the LAAV of 23.9%. Both the ACV and LAAV for modified sample did not comply with the requirements. Meanwhile, the peak stability values are vi at 5.5% for modified sample and 5.0% for control sample. This implies that the heated aggregate experienced the decomposition of up to 20% Silica element which increased the pores inside the aggregate particle. Higher pores require more bitumen to fill in the voids. For flow values, the modified sample indicated higher values ranging from 2.9 mm to 4.7 mm as compared to control sample that shows an acceptable range from 2.2 mm to 3.8 mm. The air voids range in modified sample show a higher difference between 2.1 to 10.1%. The air voids range for the control sample is more uniform between 3.5 to 6.4%. This implies that the aggregate exposed to higher temperature has more pores due to the burning of the Silica (SiO2) inside the aggregate particle. Consequently, the range for the Voids Filled with Bitumen (VFB) is higher for modified sample, which is between 46.4 to 87.4%. For control sample, the range of VFB is more uniform, with lower range from 58.7 to 83.2%. In general, the findings provide a better understanding of the effects of the elevated temperature on the aggregate properties and asphalt mix performance. Clearly, the elevated temperature significantly affected the properties of the aggregates. Therefore, the heated aggregates are not suitable for use in the new asphalt mixture prepared for the wearing course.